Pemetaan Bioaktivitas Senyawa pada Kantung Tinta Cumi-cumi (Loligo vulgaris) Secara In Silico - Angelinus Vincentius; Yohanes Bare (Peneliti.net, 2022)
Fish resources according to the Fisheries Law are the potential of all types of fish, including molluscs (squid, and others). Squid (Loligo vulgaris) is a class of Cephalopoda, which is a nutritious food ingredient and has high economic value, but there is still lack of information about its health benefits. Loligo vulgaris has a special characteristic of ink bags that are used as a form of defense against enemies. In its application in life the ink bag always forms a waste material. Utilization of squid ink waste is still limited. The purpose of this study was to analyze and perform a virtual mapping related to the bioactivity of secondary metabolites of Loligo vulgaris. This study used an in silico approach, information on the content of compounds in squid 5,6-dihydroxyindole-2-carboxylic acid (DHICA) (CID: 119405), 5,6-dihydroxyindole (DHI) (CID: 114683) and 2-carboxyl indole (CID: 72899 ), melanin (CID: 6325610), cinnamic acid (CID:), betaine (CID: 247), and choline (CID: 305) were obtained from the NCBI PubChem database. PASS two way drug program and analyzed with Origin Pro 2021 for mapping or heatmap display. The results showed that Squid Ink (Loligo vulgaris) contains melanin, 5,6-dihydroxyindole-2-carboxylic acid (DHICA), 5,6-dihydroxyindole (DHI) and 2-carboxyl indole, cinnamic acid, betaine, and choline. has pharmacological properties as the main ingredient in therapy as anti-inflammatory (eighteen anti-inflammatory parameters), antioxidant (sixteen antioxidant parameters) and as antibacterial (eight antibacterial parameters). The conclusion that squid ink can be used as anti-inflammatory, antioxidant and antibacterial therapy.